1999
DOI: 10.1002/etc.5620180807
|View full text |Cite
|
Sign up to set email alerts
|

Molecular models of benzene and selected polycyclic aromatic hydrocarbons in the aqueous and adsorbed states

Abstract: Energy gaps between the highest‐occupied molecular orbital and lowest‐unoccupied molecular orbital (ΔEHOMO‐LUMO) for a suite of common polycyclic aromatic hydrocarbons (PAHs) in the gas‐phase were calculated with three different molecular modeling methods: semiempirical, ab initio Hartree‐Fock, and density functional calculations. Results indicate that semiempirical, Hartree‐Fock, and density functional calculations may provide useful relative HOMO‐LUMO gap information, but these methods overestimate the actua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…Betowski et al (2002) reported the excited singlet state energy at the CIS/6-31G and CIS/6-311G(d,p) level. However, the CIS excitation energies, as well as the energy obtained through the semiempirical and ab initio Hartree-Fock methods, are always higher than the experimental values (Kubicki et al, 1999). The TD-DFT excitation energies have been proved to be in close agreement with the experimental values for other molecules .…”
Section: Discussionsupporting
confidence: 50%
“…Betowski et al (2002) reported the excited singlet state energy at the CIS/6-31G and CIS/6-311G(d,p) level. However, the CIS excitation energies, as well as the energy obtained through the semiempirical and ab initio Hartree-Fock methods, are always higher than the experimental values (Kubicki et al, 1999). The TD-DFT excitation energies have been proved to be in close agreement with the experimental values for other molecules .…”
Section: Discussionsupporting
confidence: 50%
“…P olycyclic aromatic hydrocarbons (PAHs) are a group of ubiquitous hydrophobic organic contaminants (HOCs) that continue to receive considerable attention because of their toxicity, persistence, and extensive distribution in the environment (e.g., Means et al, 1980; Kubicki et al, 1999; Schwarzenbach et al, 2003). In general, the chemical state in which PAHs are present in the environment determines their fate, transport, and overall environmental effects (e.g., Schnoor, 1996; Kubicki et al, 1999; Schwarzenbach et al, 2003). At many contaminated sites, a complex suite of organic chemicals and inorganic elements are commonly present together (United States Department of Energy, 1992; National Research Council, 1994; Spiro and Stigliani, 1996).…”
mentioning
confidence: 99%
“…The importance of cation–π interactions from the perspective of environmental science and engineering, however, has gone largely unexplored. For example, it is reasonable to expect that cation–π interactions may affect the distribution of PAHs between water and mineral surfaces in low organic carbon environments (Kubicki et al, 1999; Zhu et al, 2004). Cation–π interactions may also influence the relative toxicities of PAHs and heavy metals that co‐exist in aqueous solution, because their association with one another would probably alter their transport across cell membranes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…During the last 10 years, a wide range of smaller and larger systems has been investigated. This includes the complexation of aluminium in the soil solution (Tunega et al , 2000), molecular models of organic acids (Trout et al , 2005), interactions of organic chemicals with aluminium oxides (Vermohlen et al , 2000), benzene and aromatic hydrocarbons in the adsorbed state (Kubicki et al , 1999), the interaction of herbicides with clay surfaces (Tunega et al , 2004) and organic moieties (Haberhauer et al , 2001), as well as the interactions of aromatic hydrocarbons and soil organic matter (Kubicki & Apitz, 1999). The various studies involved, for example, water as a natural solvent in the contact with surfaces of kaolinite minerals, intercalation mechanisms for different clay minerals, adsorption of phenoxyacetic acid derivatives on kaolinite and montmorillonite, and interaction of organic functional groups with phenoxyacetic acid derivatives.…”
Section: Introductionmentioning
confidence: 99%